Pimping the welfare system : empowering participants with economic, social, and cultural capital - Woodward, Kerry C., 1975- (Lexington Books, 2013)
Pimping the System is an ethnographic study of two welfare offices that empowered welfare-reliant women by providing dominant economic, social, and cultural capital in ways that acknowledged and respected the types of capital participants already possessed. It highlights ways that policy makers and front-line workers can best assist welfare participants, and shows the potential for welfare programs to be sites of individual and community empowerment.